Critical Thinking Skills and Learning Outcomes by Improving Motivation in the Model of Flipped Classroom (Universitas Negeri Semarang, 2019)
The study was based on students' high motivation for gadgets but low in learning. The renewal of learning based on active, innovative, creative, efficient and fun learning (PAIKEM) that is the Flipped Classroom model and additional variables (motivation) is required to improve the process of critical thinking skills and student learning outcomes. The purpose of this study was to analyze the effectiveness and influence of the Flipped Classroom Model towards the ability to think critically and student science learning outcomes of students by increasing their motivation. The method used in this study was an experiment with the Control Group Post-test – Only Design. The sample comprised of 121 students from 4 elementary schools in Pati. The data collection consisted of performance tests to measure critical thinking skills and learning outcomes while questionnaires to measure student’s learning motivation. The data were analyzed using the average difference test and single line regression. The analysis result of the average difference test showed that Asymp. Sig. (2-tailed) of 0.000 and result of single line regression Asymp. Sig. (2-tailed) of 0.000 (sig < 0.05). The results in this study showed that Model Flipped Classroom learning is effective in improving the ability of critical thinking, science learning outcomes and student motivation, there is positive influence between learning motivation and critical thinking skills and student learning outcomes science.